Perancangan User Experience pada Situs Web Jaringan Inovasi Pelayanan Publik Nasional (JIPPNAS) dengan menggunakan Metode Design Thinking - Fierhan Arzza Ardhana; Satrio Hadi Wijoyo; Suprapto Suprapto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
In order to propogate innovation for service providers, the Government through The Ministry of Administrative andBureaucratic Refom of the Republic of Indonesia (Kemenpan RB) held a Public-Service Innovation Competition (KIPP). In order to accomodate incoming innovations, it is necessary to have a medium to disseminate, as well as become a forum for incoming innovations so that they can inspire and be utilized by other public service providers to accelerate the development of these innovations. Kemenpan RB Stakeholders require the National Public Service Innovation Network (JIPPNAS) website to be made based on the guidelines for Minister of PANRB Regulation No. 89 in 2020. Based on these needs, researchers provide a solution by designing the user experience for JIPPNAS website which creates the final result in the form of a high fidelity prototype. In the process of designing the interface, the author prefer the method of design thinking. This method was chosen because it focuses on the user in the design process. The design thinking method consists of five stages, which is; Empathize, define, ideate, prototype, dan testing. The design of the solution is then measure based on three aspects, including pilot study, evaluation of user testing, and evaluation using the User Experience Questionnaire (UEQ). From the test results using the UEQ, the mean value on each UEQ scale is in the positive category, with all UEQ scales in the excellent category, except for the novelty scale, which is in the good category.